Effectiveness of Using Textbooks Based on Metacoginitive Skills on Student’s Learning Outcomes - Andi Tenri Ola Rivai (Indonesian Journal of Educational Studies, 2022)
Metacognition skills are related to planning skills, prediction skills, monitoring skills, and evaluation skills. This study aims to determine the effectiveness of using textbooks based on metacognition skills on learning outcomes. This research is a quasy-experimental research with The Nonequivalent Control Group Design. This research was conducted at SMAN 9 Makassar. The research samples were students of class XI IPA 2 as the experimental class and XI IPA 3 as the control class. Data collection techniques were carried out using tests in the form of pretest-posttest. The data analysis used is descriptive statistics and inferential statistics. The results of the study showed α < 0.05 (0.00 < 0.05) which means that there is a significant effect of the use of textbooks based on metacognition skills on learning outcomes. It can be said that textbooks based on metacognition skills are effectively used in the learning process